Evaluation of Korean Firefighters' Fitness Using Candidate Physical Ability Test: Pilot Study - Ji-Been Kim; Kyung-Tea Kim; Young-Seuk Cho; Dong-Il Seo; Wook Song; Han-Joon Lee; Hyun-Joo Kang; Chung-Gun Lee; Yeon-Soon Ahn; Jung-Jun Park (Asian Society of Kinesiology, 2022)
OBJECTIVES The Candidate Physical Ability Capability Test (CPAT) is a complex performance test to assess whether firefighters have sufficient ability to meet the physical demands of firefighting, and is widely used in many countries, especially in North America. In South Korea, however, simple basic physical fitness assessments are still used for firefighters' fitness evaluation. Here, we report the physical fitness of Korean firefighters using the CPAT for the first time in Korea. METHODS Eighteen male Korean firefighters aged between 20 to 30 years participated in this study. All subjects were measured for maximum oxygen consumption (VO2max) by using gas analyzer and cycle ergometer before CPAT. On a separate day, each subject performed CPAT with the best effort. Each subject's oxygen consumption (VO2), heart rate (HR) and completion time were measured during the CPAT. The results of CPAT were analyzed based on VO2max and HRmax and compared to the those of previous study from North American firefighter candidates. RESULTS VO2max was significantly (p< .001) lower and HRmax was significantly (p< .05) higher in Korean firefighters (45.4±4.6 ml/kg/min and 194.2±2.1 beat/min) than American firefighter candidates (53.0±7.4 ml/kg/min and 188.0±8.0 beat/min). During CPAT, Korean firefighters showed 69.4±15.8 %VO2max and 87.6±7.8 %HRmax and American firefighter candidates had 73.1±8.0 %VO2max and 90.1±5.3 %HRmax, but these were not statistically significant. However, the completed time of CPAT was significantly slower in Korean firefighters than American firefighter candidates (726.8±84.6 sec vs. 512.0±51.0 sec, p<.001). CONCLUSIONS Korean firefighters have lower cardiorespiratory endurance capacity and CPAT performance than American firefighter candidates. In addition, Korean firefighters did not complete the CPAT within the pass time limit. It suggests that Korean firefighters need to improve more physical ability for physical demands of firefighting.